Performance analysis of surfing: A review - Farley, O. R. L.; Abbiss, C. R.; Sheppard, J. M. (The Journal of Strength and Conditioning Research, 2017)
Despite the increased professionalism and substantial growth of surfing worldwide, there is limited information available to practitioners and coaches in terms of key performance analytics that are common in other field-based sports. Indeed, research analyzing surfing performance is limited to a few studies examining male surfers' heart rates, surfing activities through time-motion analysis (TMA) using video recordings and Global Positioning Satellite (GPS) data during competition and recreational surfing. These studies have indicated that specific activities undertaken during surfing are unique with a variety of activities (i.e., paddling, resting, wave riding, breath holding, and recovery of surfboard in the surf). Furthermore, environmental and wave conditions also seem to influence the physical demands of competition surfing. It is due to these demands that surfers are required to have a high cardiorespiratory fitness, high muscular endurance, and considerable strength and anaerobic power, particular within the upper torso. By exploring various methods of performance analysis used within other sports, it is possible to improve our understanding of surfing demands. In so doing this will assist in the development of protocols and strategies to assess physiological characteristics of surfers, monitor athlete performance, improve training prescription, and identify talent. Therefore, this review explores the current literature to provide insights into methodological protocols, delimitations of research into athlete analysis and an overview of surfing dynamics. Specifically, this review will describe and review the use of TMA, GPS, and other technologies (i.e., HR) that are used in external and internal load monitoring as they pertain to surfing.